2009
DOI: 10.1590/s1519-566x2009000500008
|View full text |Cite
|
Sign up to set email alerts
|

Eufriesea violacea (Blanchard) (Hymenoptera: Apidae): an orchid Bee apparently sensitive to size reduction in forest patches

Abstract: Edited by Fernando B Noll -UNESP Neotropical Entomology 38(5):610-615 (2009) ABSTRACT -Eufriesea violacea (Blanchard) is a very seasonal euglossine species, more frequently found in the southern and southeastern regions of Brazil. A number of studies have revealed large variations in the abundance of males of this species present in Atlantic Forest remnants throughout both regions. In this paper, we report variations in the abundance of E. violacea males sampled in several forest patches of different siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
4
18
0
1
Order By: Relevance
“…Based on our findings, we suggest that, in addition to other euglossine species that have been pointed out as potentially more sensitive to habitat disturbance (Powell and Powell 1987;Tonhasca et al 2002;Giangarelli et al 2009), Eg. annectans is another Euglossini species sensitive to anthropogenic interference.…”
Section: Discussion/ Conclusionsupporting
confidence: 56%
See 1 more Smart Citation
“…Based on our findings, we suggest that, in addition to other euglossine species that have been pointed out as potentially more sensitive to habitat disturbance (Powell and Powell 1987;Tonhasca et al 2002;Giangarelli et al 2009), Eg. annectans is another Euglossini species sensitive to anthropogenic interference.…”
Section: Discussion/ Conclusionsupporting
confidence: 56%
“…Some euglossine species are apparently sensitive to environmental disturbances (Powell and Powell 1987;Tonhasca et al 2002;Giangarelli et al 2009;Nemésio 2013), such as forest fragmentation and reduction in fragment size (Powell and Powell 1987;Sofia and Suzuki 2004;Giangarelli et al 2009). Apart from reductions in the abundance of orchid bees in forest fragments of reduced size, studies have shown that some species may have stronger dispersal limitations in fragmented landscapes, and the type of matrix may also affect the dispersal of some species of the group differently (Powell and Powell 1987;Milet-Pinheiro and Schlindwein 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that insects, mainly bees, can be used as indicators in studies on the effects of habitat fragmentation (Brown 1991), our data show that at least in the region studied, Eulaema nigrita can be used as a bioindicator of environmental perturbation in long-term studies for monitoring forest fragments. Similarly, Eufriesea violacea can be a bioindicator of conservation in forest habitats (Sofia & Suzuki 2004, Giangarelli et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…In the Neotropics, several species of Euglossini bees, also known as orchid bees, have been the focus of genetic studies over the last decade, since it has been suggested by different authors that some species of this group of bees could be adversely affected by deforestation and habitat fragmentation (Giangarelli et al 2009; Electronic supplementary material The online version of this article (doi:10.1007/s13592-014-0329-7) contains supplementary material, which is available to authorized users. 2011).…”
Section: Introductionmentioning
confidence: 99%